The role of gelam honey in modulating the immune reponse of sepsis in animal model / Mustafa Kassim - Kassim, Mustafa (2012)
Persistent systemic inflammatory response syndrome is a serious health condition that may lead to multiple organ dysfunction, organ failure, and ultimately death. It leads to both acute inflammation, caused by either infective (microbes or lipopolysaccharide [LPS]) or non-infective (chemicals) sources, and sepsis, an infection caused by a lethal dose of LPS (endotoxemia). These conditions have similar inflammatory mediators such as cytokines, nitric oxide (NO), high-mobility group box-1 (HMGB1), and heme oxygenase-1 (HO-1), suggesting that they may result from similar pathogenic mechanisms. Previous studies have investigated the applications of natural products in targeting these inflammatory mediators. Honey, for example, is used to treat inflammation and heal wounds. Gelam honey is most commonly in Malaysia. The floral source of Gelam honey is Melaleuca cajuputi Powell, traditional Melaleuca cajuputi Powell has been used to treat many diseases and it has medicinal antiseptic, antibacterial, anti-inflammatory, and anodyne properties. However, it is currently unknown whether Gelam honey has a protective effect against systemic inflammatory response during acute inflammation and sepsis. We first investigated the effects of honey, honey methanol extract (HME), and honey ethyl acetate extract (HEAE) on acute inflammation, using animal models. These products inhibited edema and pain, in correlation with their potent inhibitory activities against NO and prostaglandin E2 (PGE2) in all models. Phenolic compounds have been implicated in these inhibitory activities. We also evaluated the anti-inflammatory activity of Gelam honey extracts using High-Performance Liquid Chromatography (HPLC) and liquid chromatography–mass spectrometry (LC-MS). Subsequently, HME and HEAE were tested in vitro for their effect on NO production in stimulated macrophages, as well as for their effects on tumor necrosis factor-α (TNF-α) cytotoxicity in L929 cells. These extracts protected cells against TNF cytotoxicity and inhibited NO production, with HEAE exhibiting greater activity. Moreover, we investigated the effect of the intravenous injection of honey in rats with LPSinduced endotoxemia. We found that cytokines (TNF-α, IL-1β, and IL-10), HMGB1, and NO levels decreased, and HO-1 levels increased significantly in the honey-treated groups. We also found that Gelam honey protects organs from lethal doses of LPS, as evidenced by improved blood parameters, reduced neutrophil infiltration, and decreased myeloperoxidase activity, as well as reduced mortality in honey-treated groups compared with untreated groups. We also examined the ability of Gelam honey to scavenge peroxynitrite during immune responses mounted by the murine macrophage cell line RAW 264.7. Significantly, improved viability of LPS/IFN-γ-treated RAW 264.7 cells and significant inhibition of NO production were observed, similar to those observed with an inhibitor of inducible NOS. In addition, Gelam honey inhibited peroxynitrite production from the synthetic substrate SIN- 1 as well as peroxynitrite synthesis in LPS-treated rats (endotoxemia). Thus, by suppressing the production of cytotoxic molecules such as NO and peroxynitrite, honey may attenuate the inflammatory responses that lead to cell damage and, potentially, to cell death. The results therefore suggest that honey has therapeutic uses for a wide range of inflammatory disorders.